Review of The Black Urban Atlantic in the Age of the Slave Trade, by Jorge Cañizares-Esguerra et al., & The Brink of Freedom; Improvising life in the Nineteenth-Century Atlantic World, by David Kazanjian - Klooster, Wim (European Review of Latin American and Caribbean Studies, 2017)
The Black Urban Atlantic in the Age of the Slave Trade, by Jorge Cañizares-Esguerra et al. University of Pennsylvania Press, 2016The Brink of Freedom; Improvising life in the Nineteenth-Century Atlantic World, by David Kazanjian. Duke University Press, 2016